The effects of different types of bedding on the performance, skeletal and behavioral characteristics, hygienic and immunity conditions of suckling Holstein calves - Hosseini, S. M. J.; Tanha, T.; Maghsoodi, H. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
To investigate the effects of bedding types on the performance, skeletal and behavioral characteristics, health and immunity conditions of suckling Holstein calves, an experiment was conducted in a completely randomized design using 80 Holstein calves. The calves were distributed over 5 treatments and 4 replicates (each replicate included 2 male and 2 female calves). The 5 experimental treatments werechaff, straw, bagasse, sand, or mat. The results showed that the highest feed intake was related to the sand and chaff beddings and the highest weight gain (P<0.05) was found for the chaff, straw and sandbeddings . Withers height was highest and lowest for straw and mat treatments, respectively (P<0.05). The longest standing and resting times in calf behavior (P<0.05) were found for the sand and straw treatments, respectively. In cleanness, nose, eye, and joint scorings, the highest amount of con-tamination was related (P<0.05) to the mat and sand treatments . For immunity parameters, bagasse treatment showed the highest level of eosinophils (P<0.05) compared to the other treatments. Accord-ing to the results, it can be concluded that the straw bedding has better characteristics for growth, be-havior, and health of calves compared to the other beddings.